Respiratory surveillance in mineral dust-exposed workers. Issue 1 (March 2020) - Wood, Clare; Yates, Deborah
Recently, there has been a worldwide resurgence in pneumoconiosis, or pulmonary fibrosis due to occupational mineral dust exposure. In Queensland, Australia, there has been a re-emergence of coal workers' pneumoconiosis and silicosis. Some coal mining communities have experienced a resurgence of progressive massive fibrosis in the USA and a worldwide epidemic is occurring of accelerated silicosis due to exposure to artificial stone. These diseases are all preventable and should not be occurring in the 21st century. Best practice prevention includes reduction of exposure to mineral dusts or, ideally, prevention of exposure altogether. However, where dust exposure has occurred, respiratory surveillance can provide a strategy for early disease detection. It is important to identify early signs of occupational lung disease at a stage where intervention may be beneficial, though it must be acknowledged that progression may occur even after cessation of exposure to dusts. Respiratory surveillance should be distinguished from population screening and case finding, which are different methods used for disease investigation and control. Designing an ideal respiratory surveillance programme is challenging, as there is no single test that accurately identifies early disease. Several different respiratory disorders may occur related to the same exposure(s). Physicians organising and interpreting tests used in respiratory surveillance must be aware of the broad range of potential work-related respiratory conditions, complexities in diagnosis, and appropriate interpretation of the exposure history, as well as current management options. A working knowledge of the compensation and medicolegal avenues available to workers in individual jurisdictions is also useful. Key points: Mineral dust exposure causes a number of conditions, including those specific to dust exposures, such as the pneumoconioses (or pulmonary fibroses due to mineral dust exposure), and others that may additionally be related to other causes, such as COPD. Identification of multiple conditions using respiratory investigations requires expert interpretation and understanding of the range of potential conditions. The frequency and content of a respiratory surveillance programme will vary according to the relevant occupational exposures, and be affected by both medical and nonmedical factors, including the background prevalence of local diseases. A programme will also need to consider other factors such as local legislation, availability of resources, worker convenience and cost. Educational aims: To identify the large range of respiratory diseases caused by exposure to mineral dusts and identify the range of tests that may be used in a surveillance programme for occupational respiratory disorders. To highlight difficulties that might be experienced by medical practitioners in designing and operating an effective surveillance programme, while incorporating rapidly advancing medical technology and practice. Organising and interpreting respiratory surveillance for mineral dust-exposed workers requires specialist knowledge and understanding of the potential range of diseases, as well as a detailed occupational history http://bit.ly/37KXSE4